The role of miR-29c/B7-H3/Th17 axis in children with Mycoplasma pneumoniae pneumonia - Qing-ling Li; Yin-yin Wu; Hui-ming Sun; Wen-jing Gu; Xin-xing Zhang; Mei-juan Wang; Yong-dong Yan; Chuang-li Hao; Wei Ji; Zheng-rong Chen (BMC, 2019)
Abstract Background Mycoplasma pneumoniae (M. pneumoniae) is one of the most common causes of community-acquired pneumonia in children. Recent studies demonstrated that the incidence of severe or fatal M. pneumoniae was gradually increasing, which may be related to the excessive inflammation. However, the exact pathogenesis of excessive inflammation in Mycoplasma pneumoniae pneumonia(MPP) is still unclear. This study aimed to reveal the role of miR-29c/B7-H3/Th17 axis in children with MPP. Methods Children hospitalized in Respiratory Department during Jan. 2014 to Dec. 2015 were enrolled. All children enrolled was confirmed with MP infection using real-time PCR and ELISA. Children were excluded if they were co-infected with other pathogens. A total of 52 children with MPP and 26 controls were enrolled. miR-29c expression in monocytes of children with MPP was determined by real-time PCR and soluble B7-H3 (sB7-H3) and IL-17 were determined by ELISA, and explore their clinical significance. miR-29c overexpression and silencing technology and luciferase reporter assay were performed to confirm whether B7-H3 is the direct target of miR-29c. The levels of transcription factor ROR-γt in CD4+ T cells and cytokine IL-17A in supernatant were detected after stimulated by different concentrations of B7-H3 fusion protein in vitro. Results Of all 52 children with MPP, the mean age of the children were 77 ± 33 months, and 23 cases were male accounting for 44.2%. Nineteen cases had pleural effusion accounting for 36.5%. Children with MPP had significantly lower level of miR-29c and higher level of sB7-H3 and IL-17 compared to controls (both P < 0.05). The level of miR-29c significantly increased during convalescent phase compared to that of acute phase while sB7-H3 and IL-17 significantly decreased during convalescent phase (both P < 0.05). There was a positive correlation between the level of sB7-H3 and IL-17 in children with MPP during acute-stage (r = 0.361,P = 0.009). Children with MPP combined with pleural effusion had significantly higher level of sB7-H3 compared to those without pleural effusion (9952.3 ± 3065.3 vs. 7449.7 ± 2231.5, pg/ml), and the levels of sB7-H3 was positively correlated with the number of days of fever. The level of miR-29c was negatively correlated with M. pneumoniae specific IgG, IgM level. High concentrations of B7-H3(15μg/ml) could enhance ROR-γt expression and increase IL-17A. Functional studies based on luciferase reporter assay and immunofluorescence staining suggested that B7-H3 is the direct target of miR-29c, and miR-29c silencing or overexpression could up- or down-regulate the expression of B7-H3 in THP-1 cells. Conclusions The axis of miR-29c/B7-H3/Th17 plays a vital role in children with MPP through excessive inflammation. miR-29c and B7-H3 may be the new target for the prevention and treatment of MPP, and may be the novel and potential biomarkers for the assessment of prognosis.